THE EFFECTIVENESS OF USING STIMULER APPLICATION AND VOCABULARY MASTERY ON SPEAKING SKILLS IN CIREBON VOCATIONAL HIGH SCHOOL - Salsa Ayu Denistiani; Lili Sururi Asipi; Dwi Nopiyadi (Tomorrow's Education Journal, 2025)
This study aims to examine the effectiveness of using the Stimuler application and vocabulary mastery on speaking skills at vocational high schools in Cirebon. A quantitative method with a survey design was employed, involving 149 tenth-grade students from SMK Kartika XIX Kota Cirebon and SMK Ponpes Manbaul Ulum in the 2024/2025 academic year. The research instruments consisted of a Stimuler usage questionnaire, a vocabulary test, and a speaking test. Multiple regression analysis revealed that the Stimuler application had a significant effect on speaking skills (t = 12.256, p < 0.05), as did vocabulary mastery (t = 3.839, p < 0.05). The F-test further indicated that both variables simultaneously had a significant effect (F = 84.961, p < 0.05), contributing 53.8% to the variance in speaking skills (R² = 0.538), while the remaining 46.2% was influenced by other factors beyond this study. These results suggest that integrating the AI-based Stimuler application with vocabulary mastery is effective in enhancing vocational students’ speaking proficiency and creating a more interactive and engaging learning environment.